2012
DOI: 10.1177/0040517512458341
|View full text |Cite
|
Sign up to set email alerts
|

The effect of quarantine-level gamma irradiation on cotton fiber and its subsequent textile processing performance

Abstract: Quarantine treatments of raw cotton fiber with gamma irradiation are known to have an adverse effect on fiber properties and thus could have an effect on processing into textile products. In this study, the effects of such irradiation treatments on two different cottons, cultivars of Upland and Extra Long Staple, were studied. Even at low dosages, gamma irradiation affects the physical properties of the fiber, with these effects becoming more apparent and significant as the dosage increased. While the affect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Takács et al [78] ascribed observed increasing absorbance in the spectral regions that are representative of OÀ ÀH stretching [88] to increased intermolecular hydrogen bonding at the expense of intramolecular hydrogen bridges. Molecular degradation is further supported by reports of radiation-induced depolymerization and lower molecular weight [78,81,83] and decreased paracrystalline regularity [81,82]. For neutron exposure of cotton, onset of fibrillation has been reported at a dose of 10 11 neutrons cm À2 [89].…”
Section: Potential Effects Of Radiation On Evidence: Fibers and Hairmentioning
confidence: 70%
See 3 more Smart Citations
“…Takács et al [78] ascribed observed increasing absorbance in the spectral regions that are representative of OÀ ÀH stretching [88] to increased intermolecular hydrogen bonding at the expense of intramolecular hydrogen bridges. Molecular degradation is further supported by reports of radiation-induced depolymerization and lower molecular weight [78,81,83] and decreased paracrystalline regularity [81,82]. For neutron exposure of cotton, onset of fibrillation has been reported at a dose of 10 11 neutrons cm À2 [89].…”
Section: Potential Effects Of Radiation On Evidence: Fibers and Hairmentioning
confidence: 70%
“…Beginning at 25 kGy gamma irradiation, and steadily increasing with dose, there were significant changes in the FTIR absorbance spectra of cotton-cellulose fibers, with a notable increase in the characteristic carbonyl region, 1730-1750 cm À1 [78]. Contrastingly, Van der Sluijs and Church [81] saw no change in FTIR carbonyl absorbance with 74 kGy gamma. Takács et al [78] ascribed observed increasing absorbance in the spectral regions that are representative of OÀ ÀH stretching [88] to increased intermolecular hydrogen bonding at the expense of intramolecular hydrogen bridges.…”
Section: Potential Effects Of Radiation On Evidence: Fibers and Hairmentioning
confidence: 89%
See 2 more Smart Citations
“…Recently, cellulosic biomass has been irradiated with 60 Co gamma rays to modify its physicochemical properties and extend its usefulness (Le Moigne et al 2017;Misra et al 2020). The physicochemical properties of the irradiated materials differ greatly from those of the virgin cellulosic biomass (Sluijs and Church, 2013;Le Moigne et al 2017). Various functional groups have been grafted onto the molecular chains of cellulose via irradiation to promote its mechanical, optical, and antibacterial properties (Tataru et al 2020;Söylemez et al 2018; Barsbay and Güven, 2019).…”
Section: Introductionmentioning
confidence: 99%